Enhanced NMDA receptor tyrosine phosphorylation and increased brain injury following neonatal hypoxia–ischemia in mice with neuronal Fyn overexpression - Knox, Renatta (2012)
The Src family kinases (SFKs) Src and Fyn are implicated in hypoxic–ischemic (HI) injury in the developing brain. However, it is unclear how these particular SFKs contribute to brain injury. Using neuron-specific Fyn overexpressing (OE) mice, we investigated the role of neuronal Fyn in neonatal brain HI. Wild type (WT) and Fyn OE mice were subjected to HI using the Vannucci model at postnatal day 7. Brains were scored five days later for evaluation of damage using cresyl violet and iron staining. Western blotting with postsynaptic density (PSD)-associated synaptic membrane proteins and co-immunoprecipitation with cortical lysates were performed at various time points after HI to determine NMDA receptor tyrosine phosphorylation and Fyn kinase activity. Fyn OE mice had significantly higher mortality and brain injury compared to their WT littermates. Neuronal Fyn overexpression led to sustained NR2A and NR2B tyrosine phosphorylation and enhanced NR2B phosphorylation at tyrosine (Y) 1472 and Y1252 in synaptic membranes. These early changes correlated with higher calpain activity 24 h after HI in Fyn OE mice relative to WT animals. Our findings suggest a role for Fyn kinase in neuronal death after neonatal HI, possibly via up-regulation of NMDA receptor tyrosine phosphorylation.